Rediscovery of Artemisia nortonii (Asteraceae, Anthemideae) and clarification of its type locality and geographical distribution - Guo, Xin-Qiang; Wang, Long; Yang, Qin-Er (Phytotaxa, 2022)
Rediscovery of Artemisia nortonii (Asteraceae, Anthemideae) from Dinggyê county in Xizang (Tibet), China, is reported. The type locality of A. nortonii is determined to be Tingri in southwestern Xizang, a county closely neighboring with Dinggyê, not Gyaca county in southeastern Xizang. Consultation of literature and survey of herbarium specimens indicate that this species is currently known only from Dinggyê and Tingri in the Mount Everest (Zhu Mu Lang Ma Feng) region in southwestern Xizang, not occurring in eastern and southern Xizang as previously recorded. A full morphological description, a distribution map, and color photographs are provided for A. nortonii.